River water quality analysis and pollution control strategy - Nabil, Ahmad Jazuly (Environmental and Toxicology Management, 2023)
The increase in population and the development of a city along with human activities in meeting their needs from agriculture, industry and household activities produce waste as a cause of the decline in river water quality. Method: The data used in this study were obtained from previous studies, river water sampling was carried out directly using the grab sampling method. Results: Analysis of the Metro River water obtained the results of the examination that the quality of water quality from good conditions to mild pollution. The Malang Regency Environmental Agency on the quality of the Metro River periodically from 2012 to March 2015 showed that it had exceeded the water quality standards and was polluted. The Ngringo River exceeded the water quality standards. Conclusion: The condition of the river water that exceeded the water quality standards was due to increased domestic, agricultural and industrial activities. The river water pollution control strategy uses a Progressive Strategy with aggressive water pollutioncontrol efforts.